Analisis Komprehensif Perilaku Generasi Z dalam Pemanfaatan Layanan Pusat Kesehatan Masyarakat: Tantangan Digitalisasi, Stigma Psikososial, dan Transformasi Pelayanan Kesehatan Primer di Indonesia - Riky Perdana; Devi Alviani; Sri Rahmayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The transformation of primary healthcare systems through Community Health Centers (Puskesmas) faces significant challenges in responding to the unique characteristics of Generation Z, who are digitally literate yet psychosocially vulnerable. This study aims to analyze the healthcare-seeking behavior of Generation Z at Puskesmas in Pekanbaru City and the influencing factors using the Health Belief Model (HBM) approach. A quantitative method with a cross-sectional design was employed, involving 200 Generation Z respondents. Data were analyzed using univariate and bivariate techniques with the Chi-Square (X2) test. The results indicate that while 51% of respondents are concerned about mental health issues, the utilization rate of physical services at Puskesmas remains low (36%). Bivariate analysis revealed a significant correlation between perceived barriers—such as bureaucracy and stigma—and service utilization (p=0.001), whereas digital literacy did not show a significant correlation (p=0.062). The study concludes by emphasizing the importance of modernizing services through humanistic digitalization and the reduction of social stigma to enhance Puskesmas accessibility for the younger generation in the era of epidemiological transition.